Perancangan Alat Penghalus Kotoran Kambing dengan Metode Quality Function Deployment - Lutfi Rohman Sodik; Firman Ardiansyah Ekoanindiyo (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Making fertilizer from goat dung usually requires additional materials such as fermenters, water, and dry leaves, as well as tools such as hoes, plastic sheeting, buckets, tarpaulins, and pestles. The process of making manure by farmers in Ngadirejo village, Kromengan district, takes quite a long time because the destruction of dry goat dung is still done manually by pounding. This study aims to design a goat dung crusher machine to optimize the destruction process. The method used to design this machine is Quality Function Deployment (QFD), which is an approach that focuses on meeting the needs of the users, in this case goat farmers. Through a questionnaire, the design attributes desired by the user are identified and translated into technical design responses. The next step is to create a design visualization and a machine prototype. The advantages of using the QFD method compared to previous methods are its ease of use, as well as increased efficiency and ergonomics compared to manual methods. This manure crusher machine is not only more efficient in terms of time and cost, but also provides comfort and safety for operators when using it. The following results were obtained from the calculations and planning in